The Effect of E-Commerce, Tax, Supervision, and Tax Audit on Value-Added Tax Revenue (Case Study on Kudus Regency Taxpayers) - Abada, Muhammad Fakhrudin Iqbaal; Winarsih, Winarsih (Universitas Islam Sultan Agung, 2024)
Internet technology has a huge influence on the world economy. More economic activities are carried out using internet media. Seeing the potential for the development of e-commerce has made business people dive into the digital world. The explosion of e-commerce is about the attraction of the business world and the state represented by the tax authorities, in this case, the Directorate General of Taxes, Central Java Regional Office in Kudus Regency. In line with the government's proposal to tax e-commerce as a source of state revenue and expenditure, awareness of the important role of e-commerce in the current digital-based business environment requires collaboration between relevant stakeholders to strive for a climate and mechanisms that encourage the development and growth of e-commerce, trade and protect the activities that take place therein. This research used a questionnaire on 185 Kudus district taxpayers registered on the marketplace using 25 SPSS data analysis. E-commerce is proven to have an influence on value-added tax revenue. Tax supervision has been proven to have an influence on Value Added Tax Revenue. The audit proved that taxes have a positive effect on value-added tax revenues. The research results show that all variables used have a positive effect on value-added tax revenues.